Teaching in English on the Rise in European Higher Education - Wachter, Bernd (International Higher Education, 2008)
In 2008, the Academic Cooperation Association, a Brussels-based European association specialized in the internationalization of higher education, has now come out with a study about English-Taught Programmes in European Higher Education. The study is based on surveys of 2,200 higher education institutions in 27 European countries where English is not the domestic language of instruction. This article presents the key findings from the original publication.